Use of l-3-n-Butylphthalide within 24 h after intravenous thrombolysis for acute cerebral infarction. (August 2020) - Wang, Mingzhe; Feng, Yu; Yuan, Yike; Gui, Liqing; Wang, Jian; Gao, Penglin; Qin, Baofeng; Sima, Dandan; Wang, Qiudong; Pan, Weidong
Highlights: In this study, we investigated the effect of the Chinese herbal extracts, l-3-n-Butylphthalide (NBP), in injection and tablet forms, on improving for the patients within 24 h after intravenous thrombolysis for acute cerebral infarction. Our findings demonstrate that compared with the control group, the NIHSS score in the NBP group was significantly improved at 90 days, and the number of patients with a mRS (modified Rakin scale) score 0–2 increased significantly. We demonstrated one very intersting result that use of NBP within 24 h after rt-PA (intravenous thrombolysis) treatment can reduce the prevalence of reocclusion of blood vessels without increasing the risk of cerebral hemorrhage. Abstract: Objective: Observe the clinical efficacy of l-3-n-Butylphthalide (NBP) in acute ischemic stroke (AIS) patients within 24 h after intravenous thrombolysis using recombinant tissue plasminogen activator (hereafter termed "IT"). Methods: One-hundred and seventy-eight patients with AIS were divided randomly into two groups: NBP and control. The former was given a NBP injection within 24 h after IT. After intravenous injection of NBP for 8–10 days, patients switched to soft capsules of NBP before or during meals. NBP treatment was continued for ≥30 days after hospital discharge. In the control group, NBP was not injected within 24 h after IT, and NBP capsules were not given after 8–10 days. Both groups were reviewed for CT or MRI 24 h after IT. The National Institutes of Health Stroke Scale (NIHSS) score was calculated. The number of patients with a modified Rankin scale (mRS) 0–2 before, 24 h, and 90 days after IT was documented. Prevalence of cerebral hemorrhage and reocclusion of blood vessels after IT was calculated. Results: There were no differences in sex, age, blood pressure, blood glucose, or cerebral-infarction types between the two groups before treatment. The NIHSS score 24 h after IT and the percentage of mRS scores 0–2 were not significantly different between the two groups. Compared with the control group, the NIHSS score in the NBP group was significantly improved at 90 days, and the number of patients with a mRS score 0–2 increased significantly. There was no significant difference in hemorrhage prevalence after IT between the two groups. Prevalence of blood-vessel occlusion after IT was significantly lower in the NBP group than that in the control group. Conclusion: Use of NBP within 24 h after IT can reduce the prevalence of reocclusion of blood vessels without increasing the risk of cerebral hemorrhage.